2017
DOI: 10.3389/frobt.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

Personality Perception of Robot Avatar Teleoperators in Solo and Dyadic Tasks

Abstract: Humanoid robot avatars are a potential new telecommunication tool, whereby a user is remotely represented by a robot that replicates their arm, head, and possible face movements. They have been shown to have a number of benefits over more traditional media such as phones or video calls. However, using a teleoperated humanoid as a communication medium inherently changes the appearance of the operator, and appearance-based stereotypes are used in interpersonal judgments (whether consciously or unconsciously). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Conscientiousness was identified in many tests as well but significantly less frequent than extraversion. The identification of extraversion agrees with several studies about the head and eye movements or gaze of humanoid robots or virtual agents [20,33,[44][45][46], as does the identification of conscientiousness [33,45]. However, the two dimensions were by no means the only possibilities.…”
Section: Summary Of the Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Conscientiousness was identified in many tests as well but significantly less frequent than extraversion. The identification of extraversion agrees with several studies about the head and eye movements or gaze of humanoid robots or virtual agents [20,33,[44][45][46], as does the identification of conscientiousness [33,45]. However, the two dimensions were by no means the only possibilities.…”
Section: Summary Of the Resultssupporting
confidence: 87%
“…It is almost certain that, due to the complexity of personality and how it is perceived, a group of users is unlikely to perceive the robot personalities under construction as similar to the archetypes without optimisation, even when the robots exhibit the most 'archetypal' behaviour. This 'self-other' discrepancy has been observed in perceiving human personalities for a long time [32], and in the perception of robot personalities as well [33]. The discrepancy should be minimised for the sake of consistent user experience.…”
Section: Goals and The Limitations Of The State Of The Art In The Eng...mentioning
confidence: 97%
“…Nvidia and ITU Copenhagen [2014] published articles on gaze controlled drones achieving primitive movements by following eye gaze of an operator although the system is not yet aimed for people with different range of abilities. Bremner [2016] and colleagues investigated effect of personality cues of a robotic tele-avatar like gesture, speech and appearance on its perception by the operator. They also reported that the perception and individual behavior of operator is subjective and vary for individuals and concluded that any human robotic system should be designed considering the user background, perception and behavior.…”
Section: Hri With Non-conventional Modalitiesmentioning
confidence: 99%
“…This might have affected the flow of the human-robot interactions, namely, the human participants might have adapted to the questions during the human-human interactions. In our follow-up studies related to personality, we always randomised the order of interactions [47]. • Subject-level engagement annotations.…”
Section: Limitationsmentioning
confidence: 99%